Tectonic Fault Control of Wetland Distribution in the Central Amazon Revealed by Jers – 1 Radar Imagery - DOI 10.5216/bgg.v19i1.15313 - B.R, Forsberg; Y, Hashimoto; A, Rosenqvist; F.P, Miranda (Boletim Goiano de Geografia, 2011)
.